Exploring the Cross-Level Impact of Counseling Satisfaction from the Longitudinal Study of Learning Outcomes: A Case Study of Economically Disadvantaged Students - Chun-Chieh, Tseng; Cheng-Ping, Chang (Advances in Social Sciences Research Journal, 2021)
This paper discusses the connotations between the learning outcomes of economically disadvantaged students and time factors. We recruited 1,053 economically disadvantaged students from a private university as participants and collected their mean scores in professional courses for 4 years. After observing the initial learning outcomes and academic growth rates of the students, this study concluded that counseling satisfaction had a cross-level moderating effect on learning outcomes. Additionally, the learning outcomes of economically disadvantaged students in professional courses exhibited decelerating growth with time, whereas cross-level counseling satisfaction had a significant influence and moderating effect on academic growth rate.